PROBLEMS OF LEARNING BIOLOGY ONLINE IN HIGH SCHOOLS - Nadiatul Khairo; Yosi Laila Rahmi (Universitas Negeri Padang, 2022)
Online learning during the Covid-19 pandemic is an educational innovation that involves elements of information technology in learning. This online learning is one of the unavoidable efforts for educational institutions so that the learning process continues during the Covid-19 pandemic in order to maintain health and prevent the spread of the virus by continuing to study from home. This study aims to describe the biology learning of students through online learning. This research is a qualitative descriptive study. The population of this study were all students of class X science. The research sample amounted to 162 students consisting of 6 classes. The sampling technique is a total sampling technique. This research is a qualitative descriptive study. Where after the data that has been obtained collected is classified according to a predetermined formula, which is described in words or sentences according to predetermined categories to obtain a conclusion. The results of this study indicate that there is an online biology lesson for students. Biology learning through online learning for students shows the highest score of all students using 100% Handphone devices and the lowest score of 0%.